Comparative Study of Proportions of Post-Operative Sepsis _ Maternity versus General Surgical Ward - Omona, Kizito (Cogent Medicine, 2021)
Post-operative sepsis tends to complicate the recovery course of many patients. Across the globe, the proportion of post-operative sepsis varied from 2.9% to 30% in various studies. To determine mean proportion of post-operative sepsis in Maternity and General Surgical wards (GSW) and establish whether there was a significant difference in the proportion of post-operative sepsis between the two departments. The design was part of an Unmatched Retrospective Cohort study of post-operative patients admitted to the Maternity and General Surgical ward over the past 6 months. Random samples of 169 respondents from Maternity and 245 respondents from GSW were compared. Mean proportion of post-operative sepsis was 4.4% and 3.1% for Maternity ward and GSW, respectively. Test statistic, Z2 (4.98) ≫, Z1 (1.96), fell in the rejection region; hence, Ho was rejected (significant difference in the proportion of sepsis). In the Maternity ward, the risk of post-operative sepsis was more among the unmarried (p = 0.023, COR = 5.550 [1.272–24.219] at 95% CI). In General Surgical Ward (GSW), emergency surgery (11.9%) and complex surgeries (16.3%) carried more risk. Risk of post-operative sepsis in maternity was more among the unmarried (27.3%). For GSW, emergency surgery (11.9%) and complex surgeries (16.3%) carried more risk. Therefore, more effort is needed to combat post-operative sepsis.
Keywords: Post-operative sepsis; surgical site infection; gulu regional referral hospital